A scalable fully printed organic thermoelectric generator for harsh environments enabled by a stable n-type polymer - Brunetti, Irene; James Pataki, Nathan; Hinojosa, Diego R.; Hawkey, Angus; Karakaya, Ozan; Rainer, Christian; Khan, Muhammad Irfan; Franke, Leonard; Mallick, Md Mofasser; Hernandez-Sosa, Gerardo; Kemerink, Martijn; Caironi, Mario; et al. (Advanced Materials Technologies, 2025)
Affordable and versatile power sources become crucial as miniaturized electronics and sensors become more widespread. Organic thermoelectric generators (TEGs), capable of tapping into wasted heat sustainably and economically, are viewed as key enablers for powering the sensor networks of the future. Until recently, the performance of n-type organic thermoelectric materials has severely lagged behind their p-type counterparts. However, reports of a stable and highly conductive n-type polymer, poly(benzodifurandione) (PBFDO), are changing this notion. Nonetheless, validation of PBFDO as a suitable ink for scalable fabrication processes and integration of the material into a scalable organic TEG have yet to be demonstrated. This work presents the development, characterization, and optimization of a PBFDO ink for use in a scalable inkjet printing process. The n-type ink is then integrated into a screen-printed origami-inspired architecture, resulting in a 21-leg PEDOT:PSS/PBFDO organic TEG capable of delivering a record-high normalized power density among reported polymer-based TEGs of 0.718 nW cm−2 K−2. Moreover, the module ambient stability is demonstrated for up to 90 d, while its use for potential applications in harsh environments is validated for a temperature range of -8 °C to 200 °C and up to 90% relative humidity, a first for organic TEGs.